2018
DOI: 10.1186/s12889-018-6205-z
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of alcohol and drug use and other health-risk behaviors among Thai secondary school students: a latent class analysis

Abstract: BackgroundAlcohol and drug use and other health-risk behaviors tend to cluster together among adolescents and contribute a large amount of harm to both themselves and to others. This paper aims to characterize secondary school students based on their clusters of health-risk behaviors and identify factors determining class membership to these behavior-clusters.MethodsData from a national school survey was used to identify clusters of alcohol and drug use and other health-risk behaviors among secondary school st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…Previous studies have highlighted the clustering of multiple risk behaviours [16,29,30,31], in particular alcohol and tobacco use, but also illicit drug use (such as cannabis use), truancy, interpersonal violence and frequent soft drink (sugar) consumption. The combination of multiple health risk behaviours found in this study reaffirms the problem behaviour theory in vulnerable adolescents [32]. “Problem behaviour theory defines risk behaviour as anything that can interfere with successful psychosocial development and problem behaviour as risk behaviours that elicit either formal or informal social responses designed to control them” [31].…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have highlighted the clustering of multiple risk behaviours [16,29,30,31], in particular alcohol and tobacco use, but also illicit drug use (such as cannabis use), truancy, interpersonal violence and frequent soft drink (sugar) consumption. The combination of multiple health risk behaviours found in this study reaffirms the problem behaviour theory in vulnerable adolescents [32]. “Problem behaviour theory defines risk behaviour as anything that can interfere with successful psychosocial development and problem behaviour as risk behaviours that elicit either formal or informal social responses designed to control them” [31].…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, Terry-McElrath et al [16] found that the frequency of energy drink consumption is significantly and positively linked with the frequency of substance use in the past 30 days, such as alcohol, cigarettes, marijuana, and amphetamines, in a sample of over 20,000 USA adolescents in grades 8 to 12. These findings suggest that substance use behaviors tend to cluster within individuals [12,38]. Our study extend previous findings by showing that even though high school students were more likely than middle school students to report energy drink consumption, middle school students who consume energy drinks are at greater risk of also using alcohol, cannabis and tobacco cigarettes than high schoolers who consume energy drinks.…”
Section: Comparison With Other Literaturesupporting
confidence: 83%
“…In an LCA model, a latent categorical variable is created to determine individuals' class membership, and their associations with predictor variables or outcome variables can be tested. This approach has been validated in numerous studies of health-related behaviors [24][25][26][27]. LCA has been conducted in previous studies to examine patterns of bullying victimization in US adolescents [21,22].…”
Section: Introductionmentioning
confidence: 99%